Zenker's diverticulum perforation due to transoesophageal echocardiography: Case report of the management of an extremely rare life-threatening iatrogenic complication. (2020) - Terryn, F.-X.; Stangherlin, P.; Mansvelt, B.
Highlights: Transoesophageal echocardiography has a low severe morbidity rate and an exceptional mortality rate. Zenker's Divertculum perforation is a life-threatening complication which may occur during this procedure and may require emergency surgery. Some techniques are described in the literature to perform a safe transoesophageal echocardiography in patients with Zenker's diverticulum when necessary. Check lists should be implemented in order to avoid foreseeable complications. Abstract: Introduction: Transoesophageal echocardiography is generally considered to be a safe monitoring and diagnostic tool. Even though the severe morbidity rate is relatively low and mortality rate exceptional, sometimes life-threatening events may occur during this procedure. Presentation of case: We described the case of a 79-year-old woman with an extremely rare case of Zenker's diverticulum perforation following a transoesophageal echocardiography and its successful management with a 6 months follow-up. Discussion: Several specific endoscopic techniques have been described in the literature in case of Zenker's diverticulum and we believe the use of check lists should be implemented. Conclusion: We hope that the documentation of this rare iatrogenic complication will remind the operators of this procedure to be aware of a documented Zenker's diverticulum and when necessary, to take the published precautions to prevent a highly severe complication.